Tanggung Jawab dan Perlindungan Hukum Terhadap Werda Notaris - Chandra Novita (Lex Renaissance, 2017)
The problems raised in this study are, first, what sort of liability does a notary having his term of office ended have against the deed made before the end of his term? Second, how is the legal protection of a retired notary in relation to the deed made before the term ending? This research is analyzed qualitatively in the form of descriptive research, and this study uses a legislative approach and a case approach with empirical juridical research. The results indicate that, first, the liability of a notary whose term of office has ended against violations of notary laws can be either administrative, civil, or criminal with various sanctions. Second, the legal protection for a retired notary in relation to the deed he makes before/after the term of office can include legal protection from the notary himself, legislative regulations, articles of criminal prosecution, and protection from the Indonesian Notary Association (INI).Keywords: Retired notary; notary liability; notary legal protection